An Improved Approach to the Direct Construction of 2‐Deoxy‐β‐Linked Sugars: Applications to Oligosaccharide Synthesis. Issue 30 (2nd May 2018) - Lloyd, Dina; Bennett, Clay S.
Abstract: A next‐generation reagent‐controlled approach for the synthesis of 2, 6‐dideoxy and 2, 3, 6‐trideoxy sugar donors in good yield and high β‐selectivity is reported. The use of p ‐toluenesulfonyl chloride and potassium hexamethyldisilazide (KHMDS) greatly simplifies deoxy‐sugar glycoside construction, and can be used for gram‐scale glycosylation reactions. The development of this approach and its application to the construction of β‐linked deoxy‐sugar oligosaccharides are described. Abstract : β‐max ! An improved protocol for the direct synthesis of β‐linked deoxy‐sugars is described. A combination of p ‐toluenesulfonyl chloride and potassium hexamethyldisilazide (KHMDS) can activate hemiacetal glycosyl donors for dehydrative glycosylations that can be performed on scales of up to several grams. The application to oligosaccharide synthesis is described.